2011
DOI: 10.1101/gad.1984311
|View full text |Cite
|
Sign up to set email alerts
|

JNK regulates FoxO-dependent autophagy in neurons

Abstract: The cJun N-terminal kinase (JNK) signal transduction pathway is implicated in the regulation of neuronal function. JNK is encoded by three genes that play partially redundant roles. Here we report the creation of mice with targeted ablation of all three Jnk genes in neurons. Compound JNK-deficient neurons are dependent on autophagy for survival. This autophagic response is caused by FoxO-induced expression of Bnip3 that displaces the autophagic effector Beclin-1 from inactive Bcl-XL complexes. These data ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
177
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(187 citation statements)
references
References 81 publications
10
177
0
Order By: Relevance
“…A recent study described a negative regulation of the transcription factor FoxO1 by XBP1s in pancreatic β cells, mediated by a physical interaction [7]. FoxO1 has key functions during aging and in the regulation of autophagy in neurons [8]. In agreement with this, an accumulation of FoxO1 was observed in the brain of XBP1-deficient mice, correlating with the enhancement of autophagy [6].…”
supporting
confidence: 65%
See 1 more Smart Citation
“…A recent study described a negative regulation of the transcription factor FoxO1 by XBP1s in pancreatic β cells, mediated by a physical interaction [7]. FoxO1 has key functions during aging and in the regulation of autophagy in neurons [8]. In agreement with this, an accumulation of FoxO1 was observed in the brain of XBP1-deficient mice, correlating with the enhancement of autophagy [6].…”
supporting
confidence: 65%
“…FoxO1 regulates autophagy by two distinct mechanisms: it enhances the transcription of a variety of autophagyrelated genes (i.e., atg5, lc3, beclin-1) [8]; and it is able to induce autophagy in the cytosol through its acetylation and direct binding to ATG7 [9] ( Figure 1A). In a paper recently published in Cell Research, Zhao and colleagues uncover a new role of XBP1u in the control of FoxO1 levels and autophagy [10].…”
mentioning
confidence: 99%
“…3B). Although it is possible that autophagy is a secondary effect induced by the abnormal accumulation of intermediate filaments in our mutants, it has been reported that JNK signaling is directly involved in the formation of autophagic vacuoles and autophagic cell death (Byun et al, 2009;Shimizu et al, 2010;Kim et al, 2011;Xu et al, 2011). We are currently studying our Mkk7 flox/flox Nestin-Cre mice to determine whether MKK7-JNK signaling acts to suppress autophagy in the developing brain.…”
Section: Role Of Mkk7 In Neuronal Differentiationmentioning
confidence: 99%
“…This increased autophagy may reflect the established role of MAPK8/9 to strongly suppress the transcriptional activity of the PPARA (peroxisome proliferator activated receptor alpha) nuclear receptor [42] that can promote autophagy through increased expression of autophagic genes [43]. This role of MAPK8/9 to suppress basal autophagy in hepatocytes is similar to the established function of MAPK8, MAPK9, and MAPK10/JNK3 (mitogen-activated protein kinase 10) in neurons to suppress basal autophagy by repression of autophagic gene expression [27]. …”
Section: Resultsmentioning
confidence: 99%
“…MAPK8/9-regulated gene expression may lead to increased autophagy, but different paradigms of MAPK8/9-regulated gene expression could lead to reduced autophagy. For example, MAPK8/9-regulated gene expression suppresses basal autophagy in neurons [27]. A similar mechanism may account for MAPK8/9-mediated repression of autophagy in hepatocytes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%